2020
DOI: 10.1002/ijop.12654
|View full text |Cite
|
Sign up to set email alerts
|

Is there “smoke without fire”? Applying the theory of values to the study of motivational aspects of ethnic stereotypes: The case of Jewish stereotypes in Russia

Abstract: Few studies have examined to what extent commonly held stereotypes reflect real intergroup differences in motivational goals. Taking a values perspective (Schwartz et al., 2012), the study examines value preferences among Jews and Russians in Russia, to assess the extent to which commonly held stereotypes reflect values of group members. Results showed that Jews reported substantially higher levels of universalism‐tolerance, benevolence (both caring and dependability), and tradition values, and lower levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“…Values can be described as cognitive constructs which define certain desirable goals. When ordered by importance, they represent people's motivations and are an integral part of stereotypes because most stereotypes are formulated in terms of a group's motivational goals, which are inherently linked to values, e.g., "Muslims want to Islamize Europe"; "Jews are greedy and mercenary" (Tartakovsky et al, 2020). Stereotypes of forced migrants manifest in FRPP discourse because they represent one of the most effective means for legitimising their exclusionist asylum agendas (Van Leeuwen, 2007;Wodak, 2020;Talay, 2020).…”
Section: Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Values can be described as cognitive constructs which define certain desirable goals. When ordered by importance, they represent people's motivations and are an integral part of stereotypes because most stereotypes are formulated in terms of a group's motivational goals, which are inherently linked to values, e.g., "Muslims want to Islamize Europe"; "Jews are greedy and mercenary" (Tartakovsky et al, 2020). Stereotypes of forced migrants manifest in FRPP discourse because they represent one of the most effective means for legitimising their exclusionist asylum agendas (Van Leeuwen, 2007;Wodak, 2020;Talay, 2020).…”
Section: Valuesmentioning
confidence: 99%
“…Although there is some evidence to suggest that the values of forced migrants could be incongruous with host country culture (Eskelinen & Verkuyten, 2020;Talay, 2017;Lewis & Kashyap, 2013), this conclusion cannot be drawn without specific data. Earlier research has demonstrated that perceptions of minority group values are rooted in unfounded stereotypes, many of which prove to be inaccurate (Tartakovsky et al, 2020;Hanel et al, 2018). It is feasible that native perceptions of FMV in Australia and Europe are derived from emotive, unrepresentative portrayals of asylum seekers from exclusionist parties.…”
Section: Introductionmentioning
confidence: 99%
“…Точность/неточность, истинность/ ложность стереотипов до сих пор составляют предмет дискуссии; в начале XXI в. исследовательские коллективы ищут различные способы проверки существующих этнических стереотипов на истинность (см. : Realo et al 2009;Allik et al 2010;Tartakovsky et al 2020).…”
Section: образ и стереотип в имагологии и этнопсихологииunclassified